The Adoption of Online Learning during the Pandemic: Issues, Challenges, and Future Directions - Micabalo, Kingie; Poliquit, Winnie Marie; Ibañez, Estela; Pabillaran, Robert; Malait, Carla; Cano, Jesszon (JPAIR Institutional Research, 2021)
The Covid19 Pandemic has shifted the entire momentum of the traditional education processes into an environment where students experience difficulties in the E-Learning program. This study determines the challenges encountered in the duration of the E-learning and its' effect on students' perceived learning and satisfaction during the Pandemic. The investigation study formulated an aggregate of 313 respondents on a snowball inspecting strategy. Frequency and simple percentage, weighted mean, Chi-Square Test of Independence, and One-way ANOVA were used to treat and interpret the data. The findings revealed that the students encountered difficulties through course quality, peer interactions, learning diversification, user-friendliness, and course design. Additionally, it was revealed that how they perceived these difficulties affects their perceived learning and satisfaction in the E-learning process. It was found out also that a higher level of challenges would associate with dissatisfaction and lower student perception in education. The study concluded that E-learning is a platform that should be present in the teaching and learning modalities in all institutions regardless of the situation. Additionally, the course quality, peer interactions, learning diversification, user-friendliness of the process, and its course contribute to increasing the student's perceived satisfaction in E-learning. Generally, the impact of the Covid 19 pandemic provides a manifestation that to improve student perceived learning and satisfaction; there is a need to intensify the execution in the administration, teachers, and the learning management systems used in a Higher Education Institution.
Keywords: Education; E-Learning process; student learning and satisfaction; non-experimental descriptive correlational; Mandaue City; Philippines